Prevalence and associated factors of breastfeeding in women with gestational diabetes in a University Hospital in Thailand - Preeyaporn Jirakittidul; Nalinee Panichyawat; Benjaphorn Chotrungrote; Athitaya Mala (BMC, 2019)
Abstract Background Gestational diabetes mellitus (GDM), which is a medical complication that develops during pregnancy, is associated with several long-term health problems. Despite several benefits of exclusive breastfeeding (EBF), including reduction in long-term health problems in mothers with GDM, few studies have investigated breastfeeding in women with GDM and information in the Thai population is lacking. The aim of the study was to determine the prevalence of breastfeeding and the factors associated with breastfeeding during the first six months postpartum in women with GDM. Methods A questionnaire-based prospective study was conducted during November 2014 to June 2017. Study participants were first interviewed on the second day post-delivery, and then by telephone at 6 weeks, 3 months and 6 months postpartum. Breastfeeding assessment based on infant feeding practice in the last 24-h period was classified according to World Health Organization definitions. Results A total 229 women were enrolled in this study. Prevalence of any breastfeeding at 24 h, 6 weeks, 3 months, and 6 months postpartum was 28.8% (n = 66), 94.3% (n = 214), 71% (n = 154), and 49.8% (n = 104), respectively. Prevalence of EBF was 35.9% (n = 78) at 3 months, and 23% (n = 48) at 6 months after delivery. Maternal intention to breastfeed for 6 months was an independent predictor for both 6 months EBF (RR 16.38; 95% CI 2.29, 116.99) and any breastfeeding (RR 2.65; 95% CI 1.65, 4.25). Breastfeeding initiation within 24 h postpartum (RR 1.38; 95% CI 1.08, 1.76) and being a government officer or private business owner (RR 1.66; 95% CI 1.03, 2.68) were independent predictors of any breastfeeding and EBF for 6 months, respectively. Conclusion The prevalence of breastfeeding in Thai women with GDM was lower than the national and global target goal. Maternal intention to breastfeed for at least 6 months and breastfeeding initiation were important factors associated with 6 months' breastfeeding. In order to improve the breastfeeding rate and duration, health care providers should support women's feeding decision, emphasize the benefits of breastfeeding to enhance breastfeeding intention, seek to remove or minimize barriers to the initiation of breastfeeding and reduce mother-infant separation time.